Gender, participation and the right to health: health committees in Cape Town, South Africa - Austin, Janet Sarah (Department of Public Health and Family Medicine, 2017)
Community participation is now widely recognized as an integral part of health systems and the right to health. Health Committees are an example of participation, influenced by multiple social factors, yet little research has covered the impact of gendered power relations in health committees themselves. Committees are also deemed to be accountability structures, aiming to bolster the efforts of an overburdened health system and aid in responding to the need for often under-resourced services relating to women's and sexual orientation and gender identity (SOGI) minorities' health and sexual reproductive health rights. Current literature affirms the social mobilisation of communities via participation structures, with all committee members needing to be empowered in their roles to provide a greater reach and platform for marginalised groups as both committee and community members. A qualitative, exploratory study was undertaken to answer the question: What is the role of gendered power relations in Health Committees in the Western Cape? Multiple methods were used during March to December 2015 that included observation of Health Committee meetings, group discussions and indepth interviews. A Gender-based Analysis using African Feminist Theory was applied, with Connell's 1987 theory of gender and power as well as considerations of community participation as a function of citizenship. Findings showed that the perception of gender equality and gender relations amongst Health Committees remains largely misunderstood and unaddressed. The Draft Western Cape Health Boards and Facilities Bill of 2015 provided an unstable political backdrop during fieldwork. Democratic group processes did not nullify manipulation of gender roles, and a disconnection between leadership positions and influential agents could be seen. This was accompanied by no notable gender bias concerning health need foci and a non-discriminatory outlook towards committee participants or service recipients, however there was no action to engender such claims, such as special training or materials to support sexual and gender minorities. Adequate representation and reinforcing accountability of Health Committees remains a challenge. Gender mainstreaming in inclusive policy needs to be operationalised at facility level, and gendersensitivity training for Health Committees is a viable approach with which to address the continuing poor policy to implementation problem. The Western Cape Health Boards and Facilities Act of 2016 shows some promise towards recognising and broadening committee governance and diversity. Women and SOGI minorities must be supported in leadership roles to strengthen scaling up efforts and enable the Health Committees to function as truly accountable and participatory instruments for public health.